To get to know what is hidden - Ples-Bęben, Marta (Folia Philosophica, 2012)
Review of Manfred Lurker's book: The Message of Symbols in Myths, Cultures, and Religions. Translated by Ryszard Wojnakowski. Warsaw: Aletheia Publishing House, 2011.